The Role of the Social responsibility in assumption marketing decisions In the Banking sector A Field Study in Commercial Bank of Syria - Qasim, Samer Ahmad; Mohamad, Rami Mohamad; Ahmad, Doaa Anees (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research focuses on adopt the social responsibility in assumption marketing decisions in commercial bank of Syria. This research deals the social responsibility in addition to essence marketing decisions and its kinds and qualities. The research has evaluated performance of commercial bank of Syria and known the following Social responsibility and getting the bank in formulation marketing decisions. The researcher has arrived through personal interviews and giving out questionnaire of the employees and customers many results which is the existence positive effect of Social responsibility in assumption marketing decisions. In addition to the bank has big financial possibilities and depend on the marketing group that is able to put the suitable Social responsibility and apply them in suitable and effective way. تتمحور هذه الدراسة حول دور المسؤولية الاجتماعية في اتخاذ القرارات التسويقية في المصرف التجاري السوري، حيث تناولت الدراسة أبعاد المسؤولية الاجتماعية بالإضافة إلى ماهية القرارات التسويقية وأنواعها وخصائصها. لقد أجرت الباحثة تقييم لأداء المصرف التجاري السوري، بالإضافة إلى معرفة المسؤولية الاجتماعية المتبعة ومدى اعتماد المصرف عليها في صياغة القرارات التسويقية. ولقد توصلت الباحثة من خلال المقابلات الشخصية وتوزيع قوائم الاستبانة على العاملين إلى عدة نتائج أهمها وجود تأثير إيجابي للمسؤولية الاجتماعية في اتخاذ القرارات التسويقية، بالإضافة إلى أن المصرف يمتلك الإمكانيات المادية الكبيرة ويعتمد على كادر تسويقي مؤهل للمسؤولية الاجتماعية وتطبيقها بشكل مناسب وفعَال.